Desentralisasi Fiskal dan Perkembangan Sektor Pertanian di Provinsi Jawa Timur Tahun 2009-2013 - Ikrom Laily Shiyamah (Jurnal Administrasi Publik, 2015)
Abstract: Fiscal Decentralization and Development of Agriculture Sector in East Java Province at 2009-2013. This research examines the link between fiscal decentralization and agriculture sector development in East Java Province 2009-2013. Data on fiscal decentralization comes from National Financial Information System, while data on agriculture sector development comes from East Java Central Bureau of statistics. This research shows that East Java agriculture sector increases during 2009-2013 as seen from an increasing agricultural sector district gross domestic product. However, the widening gap of agricultural development gap persists between districts. Bivariate correlation analysis shows that general allocation fund (DAU), specific allocation fund (DAK), and district agriculture budget increases district gross domestic product of agriculture sector. However, district own source revenue is not. Keywords: fiscal decentralization, development of agriculture sector, and East Java Province Â  Abstrak: Desentralisasi Fiskal dan Perkembangan Sektor Pertanian di Provinsi Jawa Timur Tahun 2009-2013. Penelitian ini mengkaji hubungan desentralisasi fiskal dan perkembangan sektor pertanian di Provinsi Jawa Timur tahun 2009-2013. Data desentralisasi fiskal bersumber dari Dirjen Perimbangan Keuangan Daerah Indonesia dan data tentang perkembangan sektor pertanian bersumber dari Badan Pusat Statistik (BPS) Provinsi Jawa Timur. Penelitian ini menunjukkan bahwa perkembangan sektor pertanian membaik selama tahun 2009-2013. Hal itu terlihat dari naiknya kontribusi PDRB sektor pertanian pada periode tersebut. Akan tetapi, kesenjangan pembangunan sektor pertanian juga tampak semakin melebar. Berdasarkan analisis korelasi ditemukan bahwa Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK), dan dana sektor pertanian berhubungan dengan perkembangan sektor pertanian di Provinsi Jawa Timur. Sedangkan Pendapatan Asli Daerah (PAD) tidak berhubungan dengan perkembangan sektor pertanian. Â  Kata kunci: desentralisasi fiskal, perkembangan sektor pertanian, dan Provinsi Jawa Timur